PROPUESTA DE CREACIÓN DE UNA HOSTERÍA EN LA PARROQUIA DE PÓZUL, CANTÓN CELICA, PROVINCIA DE LOJA - Mosquera Jimbo, José Miguel (2016)
This investment project is performed to determine the "PROPOSAL FOR THE ESTABLISHMENT OF A PARISH IN HOSTERÍA PÓZUL, Celica Canton, Loja province", aims to conduct a study to see the feasibility to implement this type of business, for which it was necessary to approach four specific objectives such as market research, technical, legal, administrative and financial. To carry out the work of qualification, various methods and deductive, inductive, analytic, synthetic, mathematical and statistical used, and; between techniques are direct observation, literature collection, survey and interview, this allowed us to collect information to interpret, analyze and get efficient results in the development of this project. The market survey yielded information on the effective demand, which was 62712 for year one; likewise the offer identified giving an annual total of 2510, 1.19% projected growth rate of the canton, which showed that there is an unmet demand for 60172 for year one and 69660 for year ten results promote the project in question. The technical study unveiled the installed capacity of the project in regard to accommodation, restaurant and wetlands, starting to work with 50% of each of the services listed; the macro and micro location of the project and 6 project engineering is also indicated, he showed processes, distribution and supplies needed for the proper conduct of business. The administrative structure enabled design the structural, functional and positional organization, just as the manual functions are developed, the trade name of the company, which was limited liability company, with a duration of 10 years of life was established, and permissions required for proper operation is defined. In the financial study the total initial investment is $ 238,377.22, consisting of fixed assets is met; and deferred monthly working capital, the investment will be financed with 30% equity and 70% loan from the National Finance Corporation, a lending rate of 11.35%. Financial evaluation found positive cash flows for the project, the financial indicators were calculated with a discount rate of 19.90% giving a NPV of $ 1,001,057.50; the internal rate of return of 76.46% higher than the opportunity cost of capital; benefit cost 1.01 gain; Capital recovery will be at 3, 9 months and approximately 18 days; and sensitivity analysis with increased costs and decreased revenues yielded 0.99 in both periods showing that the project is feasible. Finally we conclude that the proposal in question is viable, because the applied studies indicated that will market acceptance and expected results will be favorable for future investors, so that the implementation of the inn is 7 recommended, establishing controls necessary to the projections made in order to take the respective corrective time.